Betel quid use and mortality in Bangladesh: a cohort study - Fen Wu; Faruque Parvez; Tariqul Islam; Alauddin Ahmed; Muhammad Rakibuz-Zaman; Rabiul Hasan; Maria Argos; Diane Levy; Golam Sarwar; Habibul Ahsan; Yu Chen (The World Health Organization, 2015)
Abstract Objective To evaluate the potential effects of betel quid chewing on mortality. (A quid consists of betel nut, wrapped in betel leaves; tobacco is added to the quid by some users). Methods Prospective data were available on 20 033 individuals aged 18-75 years, living in Araihazar, Bangladesh. Demographic and exposure data were collected at baseline using a standardized questionnaire. Cause of death was defined by verbal autopsy questionnaires administered to next of kin. We estimated hazard ratios (HR) and their 95% confidence intervals (CI) for associations between betel use and mortality from all causes and from specific causes, using Cox proportional hazards models. We adjusted for age, sex, body mass index, educational attainment and tobacco smoking history. Findings There were 1072 deaths during an average of 10 years of follow-up. Participants who had ever used betel were significantly more likely to die from all causes (HR: 1.26; 95% CI: 1.09-1.44) and cancer (HR: 1.55; 95% CI: 1.09-2.22); but not cardiovascular disease (HR: 1.16; 95% CI: 0.93-1.43). These findings were robust to adjustment for potential confounders. There was a dose-response relationship between mortality from all causes and both the duration and the intensity of betel use. The population attributable fraction for betel use was 14.1% for deaths from all causes and 24.2% for cancer. Conclusion Betel quid use was associated with mortality from all causes and from cancer in this cohort.